Pemberdayaan UMKM Ariezta Art melalui Peningkatan Promosi Digital dan Pengembangan Bisnis - Yayan Nuryana; Victor Prasetya; Siti Masrokhah; Arif Rahman (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
Ariezta Art is a micro-enterprise in Sidorejo Village, Pemalang Regency, producing handmade resin-based crafts. The business faces several challenges, such as limited digital marketing skills, unsystematic product design, and lack of basic financial recording. This community service program seeks to empower Ariezta Art through digital promotion training, product design assistance aligned with market demands, and basic financial literacy education. The implementation stages include identifying partner needs, preparing relevant training modules, and evaluating program outcomes. Results show improved partner capability in utilizing social media for promotion and recording daily financial transactions. Additionally, product designs have become more attractive and market-oriented. This program is expected to contribute to strengthening the competitiveness and business continuity of Ariezta Art, helping the MSME face the dynamic demands of the creative market.